2019
DOI: 10.1080/03003930.2019.1635015
|View full text |Cite
|
Sign up to set email alerts
|

Promoting neoliberal ideology in Finnish rural community development: the creation of new moral actors

Abstract: Today's political ambitions are based on the neoliberal aspiration to diminish the state's role and responsibilities, and to transfer those responsibilities to local communities and individuals in ways that idealise those communities, promising to 'give power to the people'. Instead of highlighting individualism, neoliberalism now celebrates communities and participation. This article deals with the effects of this ideology with regard to Finnish rural policy objectives. Drawing on Finnish village action progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Without LEADER, rural development at local level would be much more modest in terms of resources, agents, and modes of action. At the same time, I could argue that when municipalities leave rural development to LEADER groups, they have understood the essence of neoliberal rural development policy and also acted accordingly (see Nousiainen & Pylkkänen 2013;Husu & Kumpulainen 2019). In this sense, the choices of Finnish municipalities cannot be much faulted.…”
Section: Concluding Discussion: Broadening Perspectives On Place-base...mentioning
confidence: 99%
See 1 more Smart Citation
“…Without LEADER, rural development at local level would be much more modest in terms of resources, agents, and modes of action. At the same time, I could argue that when municipalities leave rural development to LEADER groups, they have understood the essence of neoliberal rural development policy and also acted accordingly (see Nousiainen & Pylkkänen 2013;Husu & Kumpulainen 2019). In this sense, the choices of Finnish municipalities cannot be much faulted.…”
Section: Concluding Discussion: Broadening Perspectives On Place-base...mentioning
confidence: 99%
“…The idea of responsible local communities EU and national rural policies are built on the idea that rural communities take responsibility for their own development (Nousiainen & Pylkkänen 2013;Gargano 2021). At the same time, as Husu and Kumpulainen (2019) state, rural policy objectives have required a new kind of moral behaviour as the residents are expected to be increasingly interested in the development of their communities. They also argue that in this setting, "the state and municipalities are constructed as 'others', 'outsiders' who do not naturally belong to village life" (Husu & Kumpulainen 2019, 16).…”
Section: Causal Explanationsmentioning
confidence: 99%
“…Similar harsh criticism by Husu and Kumpulainen (2019) was raized in relation to the $creation of new moral actors% as an outcome of aspirations in neoliberal policy to $empower% local communities through (among other things) participation. The critical discourse around the neoliberal (Finnish) rural development paradigm argues that "community development is not about transferring more power to local people, but rather about withdrawing government resources from communities# (Husu, Kumpulainen 2019, 895.).…”
Section: Critiques Of Democratic Participation and Autonomy In Leadermentioning
confidence: 98%
“…Since it often centres on practices at the local and individual levels, which are carried out in order to cope with problematic situations, it has been suggested that resilience thinking is inherently entwined with neoliberal ideologies (Neocleous 2013; Bracke 2016) -hence promoting liberal individualism, unrestricted competition, the deregulation of markets and reductions in public welfare expenditure (Harvey 2003). Celebrating local volunteering to cope with cutbacks is seen as supporting processes of responsibilisation (Joseph 2013;Caldwell 2015) and consolidating the neoliberal emphasis on regional growth that is already present within much rural policy (ITPS 2005;Hudson 2012;Husu & Kumpulainen 2019). Neoliberal influence also strengthens the focus on individual agency that often plays the key role in debates over rural resilience.…”
Section: Culture Unboundmentioning
confidence: 99%
“…Enlund 2020). And, while volunteer initiatives are often described as increasingly important in regional policy (Rönnblom 2014;Husu & Kumpulainen 2019), very little interest has been directed towards how such initiatives are also reflected in, and shaped by, more far-reaching public representations of this type of local response to change (Skinner et al 2016). The way in which spatial representations like the ones in Land magazine circulate has a bearing on people's worldviews as the media possesses moulding forces (Hepp 2012) that promote some perspectives on rural initiatives while discouraging others.…”
Section: Introduction and Aimmentioning
confidence: 99%